Charlie and the chocolate factory - Dahl, Roald (Viking, an imprint of Penguin Random House LLC New York, 2022)
Charlie Bucket's life is going to change forever, thanks to his miraculous mom. Willy Wonka, chocolate maker extraordinaire, has hidden five golden tickets in ordinary bars of chocolate, and the child who finds one will get the chance to visit his incredible factory. And Charlie has found one, but so have Augustus Gloop, a glutton for chocolate; Veruca Salt, a spoiled and selfish brat; Violet Beauregarde, a repulsive gum-chewer; and Mike Teavee, a television fiend. With a chocolate river, delectable confectionery and mysterious Oompa-Loompas, Mr. Wonka's factory is the most wondrous place Charlie has ever seen